Suppression of partial dislocation glide motion during contraction of stacking faults in SiC epitaxial layers by hydrogen ion implantation. (1st February 2023) - Harada, Shunta; Sakane, Hitoshi; Mii, Toshiki; Kato, Masashi
Abstract: Bipolar degradation in SiC bipolar devices, in which stacking faults (SFs) expand to accommodate the movement of partial dislocations during forward bias application, is one of the critical problems impeding the widespread implementation of SiC power devices. Here we clearly demonstrate that the movement of partial dislocations can be suppressed by proton implantation, which has good compatibility with semiconductor processing, through investigation of the contraction behavior of SFs in SiC epitaxial layers subjected to proton implantation.